2020
DOI: 10.3390/nu12113558
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antioxidant Vitamins A, C, E and Carotenoids with Cognitive Performance over Time: A Cohort Study of Middle-Aged Adults

Abstract: Carotenoids may strengthen the association of antioxidant vitamins A, C, and E with favorable cognitive outcomes over time, though a few prospective studies have examined this hypothesis. We evaluated the longitudinal data from 1251 participants in the Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study (Age at visit 1 in 2004–2009 (v1): 30–65 years). Vitamins A, C, and E dietary intakes and total and individual dietary carotenoids were computed using two 24-h recalls at v1. Cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 105 publications
(126 reference statements)
1
25
0
2
Order By: Relevance
“…However, only one recent study has examined interactions between those bioactive micronutrients and cognitive performance or decline in midlife. 43 The findings indicated that among others, there was a synergistic interaction between vitamin E and total carotenoids, particularly lycopene, whereby vitamin E was directly associated with baseline performance on a test of verbal memory at higher carotenoid levels, with antagonistic interactions detected between vitamin A and some carotenoids in relation to visual memory decline. 43 Our current study did not detect any synergistic interactions or a potential protective effect of vitamin E against incidence of all-cause or AD dementia.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, only one recent study has examined interactions between those bioactive micronutrients and cognitive performance or decline in midlife. 43 The findings indicated that among others, there was a synergistic interaction between vitamin E and total carotenoids, particularly lycopene, whereby vitamin E was directly associated with baseline performance on a test of verbal memory at higher carotenoid levels, with antagonistic interactions detected between vitamin A and some carotenoids in relation to visual memory decline. 43 Our current study did not detect any synergistic interactions or a potential protective effect of vitamin E against incidence of all-cause or AD dementia.…”
Section: Discussionmentioning
confidence: 89%
“…43 The findings indicated that among others, there was a synergistic interaction between vitamin E and total carotenoids, particularly lycopene, whereby vitamin E was directly associated with baseline performance on a test of verbal memory at higher carotenoid levels, with antagonistic interactions detected between vitamin A and some carotenoids in relation to visual memory decline. 43 Our current study did not detect any synergistic interactions or a potential protective effect of vitamin E against incidence of all-cause or AD dementia. In contrast, vitamin E and lycopene exhibited an antagonistic interaction in our study in relation to AD incidence, suggesting that interactions between carotenoids and antioxidant vitamins are patterned differently across time.…”
Section: Discussionmentioning
confidence: 89%
“…Wang et al [ 23 ] documented that 200 mg/kg of Crocin could be used to terminate epileptic seizures in fully kindled rats. The rate of loss of higher cerebral function in individuals with Alzheimer's dementia has been retarded using several dietary supplements, e.g., L and beta-carotene [ 24 ]. This clinical observation is consistent with the findings relating to the use of these agents in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Positive outcomes were also demonstrated in patients with Alzheimer′s disease who consumed a combination of xanthophyll carotenoids and omega-3 PUFAs (fish oil [ 59 ]). There is also evidence for synergistic action between vitamin E and carotenoids in supporting cognitive performance in middle-aged adults [ 60 ]. Supplementation with a combination of omega-3 PUFAs and vitamins C and E also prevented postoperative atrial fibrillation (as a condition that depends on neuronal activity), while omega-3 PUFA alone did not [ 61 , 62 ].…”
Section: Epidemiological and Clinical Evidencementioning
confidence: 99%